Kreativitas Guru dalam Mengatasi Kesulitan Belajar Siswa pada Mata Pelajaran IPS di Smp Negeri 34 Semarang Tahun Pelajaran 2017/2018 - Ulul Azmi, Frishana Selaksa; Purnomo, Arif; Mulianingsih, Ferani (SOSIOLIUM : Jurnal Pembelajaran IPS, 2019)
Teacher is an important part in the learning process. Besides teaching, the teacher should act as facilitator and motivator for students. Teachers’ Creativity is very important as a support in learning to achieve the learning objectives of the students. Efforts which are done by the teachers are showing up new various ideas, new ways that can make students active, and be able to minimize the causes of learning difficulties of students in Social Science or Ilmu Pengetahuan Sosial (IPS) subject. The research method is qualitative research, with the location of the research is in SMP Negeri 34 Semarang. The research result of teacher creativity in overcoming learning difficulties of students in Social Science subject, there were two factors, namely the internal factors and external factors, the teachers were trying in overcoming learning difficulties of students, as for the efforts that have been done by the teachers, there were obstacles that must be faced by the teachers in overcoming learning difficulties of students. Guru merupakan peranan penting dalam proses pembelajaran. Selain sebagai pengajar, guru harus berperan sebagai fasilitator dan motivator bagi siswa. Kreativitas guru sangat penting sebagai penunjang dalam pembelajaran untuk mencapai tujuan belajar siswa. Upaya yang dilakukan guru dengan memunculkan berbagai ide-ide baru, caracara baru yang dapat menjadikan siswa aktif, serta dapat meminimalisir penyebab kesulitan belajar siswa pada mata pelajaran IPS. Metode penelitian adalah penelitian kualitatif, dengan lokasi penelitian di SMP Negeri 34 Semarang. Hasil penelitian kreativitas guru dalam mengatasi kesulitan belajar siswa pada mata pelajaran IPS terdapat dua faktor yaitu faktor internal dan faktor eksternal, guru berupaya dalam mengatasi kesulitan belajar siswa, adapun upaya yang telah dilakukan oleh guru, terdapat kendala yang dihadapi guru dalam mengatasi kesulitan belajar siswa.